Adsorptive Removal of Dyes Using Crude Tree Barks: Equilibrium Isotherm and Kinetics - Keskinkan, Olcayto; Balci, Behzat (Asian Journal of Chemistry, 2013)
In this paper, the adsorptive removal of dyes (basic violet 3-BV3 and acid red 360-AR360) commonly used in various industries was investigated using Eucalyptus camaldulensis barks as an alternative tertiary treatment material. Adsorption equilibria were attained at 20 and 80 min for various initial BV3 and AR360 concentrations (in the range 20-320 mg/L). Attempts were made to fit the equilibrium data obtained using the Langmuir, Freundlich, Temkin and Dubinin-Radushkevich adsorption isotherm models. The data obtained from the E. camaldulensis studies provided very strong correlation using the Langmuir, Freundlich and Dubinin-Radushkevich adsorption isotherms models with regression coefficient (R2) values of 0.9763, 0.9837, 0.9955 for BV3, 0.9989, 0.9915, 0.9725 for AR360, respectively. Evaluation of the experimental data using the Langmuir equation revealed that the maximum adsorption capacities of E. camaldulensis barks were 40.98 and 37.59 mg/g for BV3 and AR360, respectively. The dimensionless constant separation factor of the adsorbent/adsorbate system was determined. External mass transfer was fast for BV3. Since BV3 was almost completely removed in 5 min, calculating the intra-particle diffusion constant (kid) of BV3 is not advisable. Application of the pseudo second-order kinetic model was more logical for BV3 data and second order kinetic model was best fit for AR360 data.